2020
DOI: 10.3390/microorganisms8101584
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella in Pigs: The Positive and Negative Associations with Production and Health

Abstract: A diverse and dynamic microbial community (known as microbiota) resides within the pig gastrointestinal tract (GIT). The microbiota contributes to host health and performance by mediating nutrient metabolism, stimulating the immune system, and providing colonization resistance against pathogens. Manipulation of gut microbiota to enhance growth performance and disease resilience in pigs has recently become an active area of research in an era defined by increasing scrutiny of antimicrobial use in swine producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 130 publications
(215 reference statements)
2
68
0
Order By: Relevance
“…are common and important bacterial colonizers of human and porcine guts. 15,16 It has been shown that if species of the genera Prevotella and Bacteroides co-occur in the gut, one or the other predominates, suggesting antagonistic behavior. 16 Indeed, we observed that greater relative abundances of Prevotella were associated with fewer Bacteroides in pig workers and vice-versa in cattle workers.…”
Section: Discussionmentioning
confidence: 99%
“…are common and important bacterial colonizers of human and porcine guts. 15,16 It has been shown that if species of the genera Prevotella and Bacteroides co-occur in the gut, one or the other predominates, suggesting antagonistic behavior. 16 Indeed, we observed that greater relative abundances of Prevotella were associated with fewer Bacteroides in pig workers and vice-versa in cattle workers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we were able to find some taxa associated with health, such as the Prevotellaceae family, which deserves further study. This family was also represented in the healthy farms at the ASVs level by Prevotella copri and Prevotella stercorea , two species previously found in higher abundance in suckling and weaning healthy piglets [ 18 ]. Two ASVs from the Lachnospiraceae family were also associated with healthy farms, in agreement with previous studies, where ASVs from this family were correlated with higher feed conversion ratio [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Negative correlations between animal body weight and abundance of Prevotellaceae have been described [80], while the Prevotelladominant enterotype has been associated with higher feed intake values compared to the Treponema-dominant enterotype in Duroc pigs [81]. As suggested by Amat et al [82], further analyses are required to clarify the role of specific species of Prevotella in pig performance. Within this family, Prevotella copri is the most abundant species found in pig gut microbiota after weaning.…”
Section: Microbiota Composition and Community Diversity Associated With MIX Supplementationmentioning
confidence: 93%